KeKerasan dalam rumah Tangga dalam Perspektif huKum Positif dan Hukum Islam - Rosman, Edi (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2012)
Violence takes never place in human life. But it, remains a social reality. Violence occurs in the private and the public. In the private sphere is called the domestic violence (domestic violence/KDRT). Attracting private problems into public space and confirm the existence of state laws criminalizing indicate. Criminalization of domestic violence policy is a form of protection by the state in each of its citizens. Efforts to eliminate domestic violence UUPKDRT delivery rules. The rules are there aspects of criminal and civil. The collapse of the bulkhead in criminal and civil domestic violence indicate a paradigmatic shift. To achieve the above goal, the research done by the specification is descriptive analytical research. The method used approach is the approach of juridical normative and comparative. Tehknik data collection is done through the study of documents or literature which is the main data, and then to the data collected, analyzed by the method of analysis indukatif , deductive and comparative. These results indicate that the nature of the offense and conviction of the positive law have similarities and differences with the Islamic law in the context of comparative law. The nature of crime and punishment is not vengeance or pengimbalan only but also to protect the interests of society. The difference with Islamic law, is to realize the ideals of the law / Shari’a, with meaning to realize the benefit of society in the midst of a preventive (mawani’), ta’dib (coaching) with penjeraan (zawajir) based on the values syar’i. This is the uniqueness of Islamic Criminal dikhotomik not and did not oppose the spiritual dimension values / divinity. Formulation of criminal sanctions in UUPKDRT no different from other laws. At this level looks urgency of criminal reform. Reform approach that used a global approach and policy. In addition to the above two approaches are commonly used, also, the religious approach. Thirdoriented approach to doing deals with the means of construction and reconstruction of national law deals with the means of Islamic law (fiqh) is characterized by Indonesia. Paradigmatic one bid, conceptual and theoretical generated by this paper is an update that has a paradigm of Pancasila, the purification of the criminal law with an critical integrative theory.